Service quality and customer satisfaction: a study of Bank Rakyat Simpang Tiga Branch counter service / Dayang Norasyidah Awang Taha - Awang Taha, Dayang Norasyidah (2017)
This project paper titled Service Quality and Customer Satisfaction: A study of Bank Rakyat Simpang Tiga Branch Counter Service: Uitm Sarawak, Samarahan Campus” is undertaken in the Faculty of Business and Management at Universiti Teknologi Mara. 150 respondents have involved in this survey which was conducted for one week and the data from the questionnaires were analyzed and computed as percentage and mean score. The purpose of this study is to evaluate the customer satisfaction on Bank Rakyat Simpang Tiga branch counter service quality. There were five dimensions to evaluate the customer satisfaction which are tangible, employee behavior, reliability, responsiveness and empathy. From this research, employee behavior and responsiveness is the dimension that contributes most favorable service in quality dimensions. This research also analyzed of critical factors that contributes most to satisfaction. Overall, this study provides a greater knowledge sharing in the subject of Consumer Behaviour whereby which factor will actually drives the students to know the way of improve the service quality and customer satisfaction in the banking line whenever they (students) is working in the bank or other organization that give services.